RESULTS OF DISPENSARY EXAMINATIONS IN GROWING CALVES - Abdiqaharovna, Botirova Shohista; izlanuvchisi, mustaqil (Research Focus International Scientific Journal, 2026)
This article presents the results of clinical examinations of calves aged 40-120 days on livestock farms in the Samarkand region. After 60 days, a decrease in hemoglobin, red blood cell count, hematocrit, and blood biochemistry was noted due to a slowdown in erythropoiesis in calves. It is argued that the main nutritional factors in the development of alimentary anemia in calves are an unbalanced diet, insufficient trace elements, vitamins, and minerals, below-standard sugar-to-protein and phosphorus-to-calcium ratios, and, especially, iron and zinc deficiencies.